Pengaruh Model Pembelajaran Cooperative Learning Menggunakan Media Permainan Kata Yang Hilang Terhadap Penguasaan Mufrodat Siswa Kelas 8 SMP Pondok Pesantren Al-Faruqi di Kampar - Latipah, Nur (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
The aim of this study was to ascertain the impact of a cooperative learning model on students' mastery of mufrodat at Kampar's Al-Faruqi Junior High School by means of the lost word game media. This kind of research is known as a quasi-experimental or pseudo-experimental study. The samples in this study were the VIII A and VIII B classes, and the population consisted of all 226 eighth grade students at Al-Faruqi Junior High School in Kampar. Class VII B served as the experimental group in this study, while class VIII A served as the control group. The sampling strategy used in this investigation was simple random sampling. The methods of observation, experimentation, and observation were employed in the data collection process. The methods of data collection included testing, observation, and documentation. The pre-test results from this study show that the average value or ability of students from both groups is still at a low level. The pre-test results from the experimental class showed an average value of 60.65, and the pre-test results from the control class showed an average value of 57.61. However, the control class's post-test results show that the average value remained at 58.65. Although the average value in the experimental class post-test results was 71.39, this value indicates a very significant difference. in order for students' mastery of mufrodat to be significantly impacted by the cooperative learning model that uses the lost word game media.